Depletion of keratin 8/18 modulates oncogenic potential by governing multiple signaling pathways. (27th February 2018) - Tiwari, Richa; Sahu, Indrajit; Soni, Bihari Lal; Sathe, Gajanan J; Thapa, Pankaj; Patel, Pavan; Sinha, Shruti; Vadivel, Chella Krishna; Patel, Shweta; Jamghare, Sayli Nitin; Oak, Swapnil; Thorat, Rahul; et al.
Abstract : Keratin 8/18, the predominant keratin pair of simple epithelia, is often aberrantly expressed in various squamous cell carcinomas (SCCs) including skin SCC. Its aberrant expression is correlated with increased invasiveness and poor prognosis of the same, although the underlying mechanism is still unclear. A previous report from our laboratory has shown K8‐mediated regulation of α6β4 integrin signaling and thereby tumorigenic potential of oral SCC‐derived cells. Another study on transgenic mouse model has shown that during skin carcinogenesis, K8 favors conversion of papillomas toward malignancy. In order to understand the role of K8 and allied mechanism in skin SCC, K8 was stably knocked down in a skin epidermoid carcinoma‐derived A431 cells. K8 downregulation significantly reduced the tumorigenic potential of these cells. In agreement with our phenotypic data, differential quantitative proteomics followed by IPA analysis showed altered expression of many proteins associated with biological functions including 'Cancer', 'Cellular movement', 'Cell death and survival', and 'Cellular morphology'. Some of these proteins were TMS1, MARCKSL1, RanBP1, 14‐3‐3γ, Rho‐GDI2, etc. Furthermore, to our surprise, there was a significant reduction in K17 protein stability upon loss of K8, probably due to its caspase‐mediated degradation. This was supported by altered TMS1‐NF‐κB signaling, leading to increased apoptotic sensitivity of A431 cells which in turn affected 'Cell death and survival'. Moreover, MARCKSL1‐Paxillin1‐Rac axis was found to be deregulated bestowing a possible mechanism behind altered 'Cellular movement' pathway. Altogether our study unravels a much broader regulatory role of K8, governing multiple signaling pathways and consequently regulating oncogenic potential of skin SCC‐derived cells. Database: Proteome Xchange Consortium via PRIDE database (dataset identifier PXD007206). Abstract : K8/18 is often aberrantly expressed in squamous cell carcinoma though its role in skin SCC and the underlying mechanism remains elusive. Here, by quantitative proteomics, and in vitro and in vivo experimental approaches, we demonstrated that TMS1‐NFκB‐mediated K17 degradation and MARCKSL1‐Paxillin1‐Rac1 signaling were modulated upon K8 depletion in A431‐cells. Eventually by altering 'Cell death‐survival' and 'Cellular movement' pathways, K8/18 proposed its broad‐spectrum role in skin SCC.